(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
أجريت الدراسة في أربعة مواقع تابعة لمنطقة الشيخ بدر في محافظة طرطوس؛ إذ تم توصيف عشرة طرز من الكرمة (العنب) مختلفة بالاعتماد على المعايير الدولية، أخذت القراءات لموسمي 2016 و2017، إذ تم تسجيل المواصفات المظهرية والتحليل الفيزيائي والكيميائي للعناقيد الثمرية. تباينت الطرز المدروسة في العديد من الصفات، إذ أظهرت نتائج التحليل العنقودي توزع الطرز المدروسة في مجموعتين بنسبة تباين وصلت إلى 93%، تراوح متوسط وزن العنقود بين الوسط (349.0غ) والكبير جدا (1140.45غ)، ونسبة المواد الصلبة الذائبة الكلية بين المنخفضة (12.75 %) والعالية ( 18.82 %)، والحموضة بين المنخفضة جداً (3.53 غ/ل) والمتوسطة (6.38 غ/ل). The study was conducted in four sites belonging to the Sheikh Badr district in Tartous province. Ten different types were identified according to international standards. During the 2016 and 2017 growth seasons, readings were recorded for phenotypic parameters as well as physical and chemical analysis of fruit clusters. The studied types differed in many characteristics. The results of the cluster analysis showed the distribution of the studied types in two groups with a variance of 93%. The mean weight of the cluster varied between the medium (349 g) and the large (1140.45 g). The ratio of total dissolved solids (TSS) between the low (12.75%) and high (18.82%). the acidity between the very low (3.53 g/l) and medium (6.38 g/l).